2013
DOI: 10.1194/jlr.m038869
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium scindens: a human gut microbe with a high potential to convert glucocorticoids into androgens

Abstract: Clostridium scindens American Type Culture Collection 35704 is capable of converting primary bile acids to toxic secondary bile acids, as well as converting glucocorticoids to androgens by side-chain cleavage. The molecular structure of the side-chain cleavage product of cortisol produced by C. scindens was determined to be 11β-hydroxyandrost-4-ene-3,17-dione (11β-OHA) by high-resolution mass spectrometry, 1H and 13C NMR spectroscopy, and X-ray crystallography. Using RNA-Seq technology, we identified a cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 55 publications
3
173
1
Order By: Relevance
“…Interestingly, C. scindens VPI 12708 metabolizes the 11b-hydroxyandrostenedione (11b-OHAD) product, reducing the 17-keto group to a 17a-hydroxy. 70 Previously, we reported that testosterone enhances 7a-dehydroxylating activity in C. hylemonae TN27172 72 ; however, it is unknown what effect 11b-OHAD, and its subsequent gut microbial metabolites has on bile acid 7a-dehydroxylation.…”
Section: Bile Acid 7a/7b-dehydroxylation By Intestinal Bacteriamentioning
confidence: 99%
“…Interestingly, C. scindens VPI 12708 metabolizes the 11b-hydroxyandrostenedione (11b-OHAD) product, reducing the 17-keto group to a 17a-hydroxy. 70 Previously, we reported that testosterone enhances 7a-dehydroxylating activity in C. hylemonae TN27172 72 ; however, it is unknown what effect 11b-OHAD, and its subsequent gut microbial metabolites has on bile acid 7a-dehydroxylation.…”
Section: Bile Acid 7a/7b-dehydroxylation By Intestinal Bacteriamentioning
confidence: 99%
“…In the current study, we report that the desA and desB genes from C. scindens The conversion of cortisol to 11β-hydroxyandrostenedione by C. scindens is an important step in a multi-species gut microbial endocrine pathway that results in the formation of 11β-hydroxyandrogens (9). Previous studies reveal a number of cortisol metabolites following incubation with mixed human or rat fecal bacteria included 3α,11β,17β-trihydroxy-5β-androstane, 3α,11β,17β-trihydroxy-5α-androstane, demonstrating the ability of gut microbes to form 5α-, 17β-reduced metabolites (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of RNA-Seq to identify differentially expressed genes, coupled with biochemical characterization of the recombinant gene products was necessary to determine the nucleic acid sequences encoding this bacteria steroid biotransforming pathway (9).…”
Section: Downloaded Frommentioning
confidence: 99%
See 2 more Smart Citations